14:(4\(\frac{1}{12}\)-\(\frac{21}{8}\))+\(\frac{29}{2}\).\(\frac{2}{3}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) $\frac{4}{{25}}:\frac{4}{3} = \frac{4}{{25}} \times \frac{3}{4} = \frac{3}{{25}}$
b) $\frac{3}{{14}}:\frac{6}{7} = \frac{3}{{14}} \times \frac{7}{6} = \frac{{3 \times 7}}{{14 \times 6}} = \frac{{3 \times 7}}{{7 \times 2 \times 3 \times 2}} = \frac{1}{4}$
c) $\frac{{12}}{{15}}:2 = \frac{{12}}{{15}} \times \frac{1}{2} = \frac{{12 \times 1}}{{15 \times 2}} = \frac{{6 \times 2 \times 1}}{{15 \times 2}} = \frac{6}{{15}}$
d) $\frac{{21}}{8}:6 = \frac{{21}}{8} \times \frac{1}{6} = \frac{{21 \times 1}}{{8 \times 6}} = \frac{{7 \times 3 \times 1}}{{8 \times 3 \times 2}} = \frac{7}{{16}}$
a)\(\frac{5}{12}+1-\frac{3}{7}+\frac{2}{24}-\frac{8}{14}\)
\(=\frac{5}{12}+1-\frac{3}{7}+\frac{1}{12}-\frac{4}{7}\)
\(=\left(\frac{5}{12}+\frac{1}{12}\right)+1-\left(\frac{3}{7}+\frac{4}{7}\right)\)
\(=\frac{1}{2}+1-1=\frac{1}{2}\)
b)\(-\frac{23}{4}+\frac{1}{2}+\frac{21}{4}-2\)
\(=\left(-\frac{23}{4}+\frac{21}{4}+\frac{2}{4}\right)-2\)
\(=-2\)
\(\left(\frac{-1}{4}+\frac{7}{33}-\frac{5}{3}\right)-\left(\frac{-5}{4}+\frac{6}{11}-\frac{48}{49}\right)=\left(\frac{-1}{4}-\frac{16}{11}\right)-\left(-\frac{31}{44}-\frac{48}{49}\right)=-\frac{1}{4}-\frac{16}{11}+\frac{31}{44}+\frac{48}{49}=-\frac{1}{49}\)
\(14:\left(4\frac{1}{12}-\frac{21}{8}\right)+\frac{29}{2}.\frac{2}{3}\)
\(=14:\left(\frac{49}{12}-\frac{21}{8}\right)+\frac{29}{3}\)
\(=14:\left(\frac{98}{24}-\frac{63}{24}\right)+\frac{29}{3}\)
\(=14:\frac{35}{24}+\frac{29}{3}\)
\(=\frac{48}{5}+\frac{29}{3}\)
\(=\frac{144}{15}+\frac{145}{15}\)
\(=\frac{289}{15}\)